Priming with skin-problems increases fear of clusters - Risako Shirai (Nature Portfolio, 2021)
Abstract Trypophobia is induced by viewing multiple clustered objects. To date, several studies have investigated why certain people experience discomfort when looking at clustered patterns. Recently, “involuntary protection against dermatosis” (IPAD) hypothesis was proposed to explain the causes of trypophobia. The IPAD hypothesis suggests that involuntary aversive responses to skin diseases cause discomfort in response to image clusters. However, this idea has not been fully investigated empirically. Therefore, the present study used a modified version of the priming procedure and tested whether the activation of the concept of skin-related diseases affected the evaluation of trypophobic images. In Experiment 1, participants engaged in a lexical decision task in which words related to skin problems, negative events, or neutral events were presented. Then, they evaluated the discomfort of trypophobic, negative, and neutral images. The results indicated that participants evaluated trypophobic images as more discomforting after they were exposed to skin-problem-related words, whereas the exposure to words related to skin-problems did not enhance the discomfort of negative images. These findings demonstrate that the association with skin-related problems increases the discomfort of trypophobic images. In Experiment 2, we further tested the reproducibility of the priming effect observed in Experiment 1 and investigated the effect of priming with words related to COVID-19 in the context of a spreading infection. Contrary to predictions, no priming effect was produced by either skin-related words or COVID-19-related words. Future studies should further explore the causal relationship of the association between skin disease and trypophobia.